Adhesive resin composites with ceramic nanoparticles for enhanced light extraction efficiency of sandwiched LED device structure. (December 2020) - Park, Jin Gyeong; Ji, Myeongjun; Ko, Yun Taek; Ryu, Cheol-Hui; Kim, Jeong Hyun; Choa, Yong-Ho; Lee, Young-In
Abstract: While phosphor-in-glass (PiG) technology is widely used in white light-emitting diodes (WLEDs), the adhesive layer between the PiG plate and the blue LED chip does not match their refractive indices, resulting in a reduction in efficiency. To address this issue, we applied ZrO2 nanoparticles with an average particle size of 10 nm to the adhesive layer as refractive index enhancer and light scattering additives in the form of polymer matrix nanocomposites. An adhesive layer with proper ZrO2 nanoparticles can enhance the luminous flux and efficacy of the WLED by refractive index matching, light scattering and increased view angle. The optimum ZrO2 content in the adhesive layer was identified as 9 wt.% and in this case, the viewing angle was extended by 8% and luminous efficacy was improved by about 3.1 % while maintaining uniform CCT and color bin. The methodology for improving the efficiency of LEDs demonstrated in this paper is expected to be of great help to the development of high-performance WLEDs.